Problem-Based Learning Discussion to Introduce Quality Improvement to Residents in the Perioperative Setting - Benjamin M. Kristobak; Jesse A. Snider (Association of American Medical Colleges, 2021)
Introduction Quality improvement (QI) is a growing and critical part of perioperative medical practice. However, there are few examples of educational tools to introduce new learners from anesthesiology to QI. This may contribute to a lack of enthusiasm to learn about and apply these concepts. Methods This problem-based learning discussion (PBLD) was designed to teach anesthesiology residents about QI in a way allowing for the application of core concepts in a group setting. We created this PBLD using available literature on QI in the perioperative setting. Basic concepts and terminology necessary for new learners to communicate about QI were specifically addressed. Feedback from staff anesthesiologists and resident participants in the PBLD was used to tailor it to the needs of the target learners and to reach the educational objectives. Results We delivered this PBLD in two separate learning sessions both to board-certified anesthesiologists (N = 10) and to resident anesthesiologists (N = 19) at our institution. The exercise was reviewed anonymously, and qualitative feedback was used to improve updated versions. Respondents felt that the PBLD would be improved by avoiding jargon-based humor, considering the systemic implications of QI, and limiting the overall length of the learning tool. The PBLD has been adopted as a starting point for discussions about QI in our training program. Discussion We feel this PBLD can introduce new learners to the learning objectives. This tool has provided an alternative to lectures or computer-based modules for teaching QI.